2016
DOI: 10.15446/agron.colomb.v34n2.55044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of three biowastes on the productivity potential of a sodic soil

Abstract: Three biowastes were applied to a Typic Haplustepts sodic soil in order to generate a Soil Productivity Potential (SPP) indicator derived from the biological, physical and chemical properties. The biowastes included swine manure (SM), vinasse (VS) and composted biosolids (CB) incorporated on experimental plots and left undisturbed. The assessment of the soil properties was done prior to and twice during the experiment. The biowastes produced, in general, an increase in the SPP, being higher that of swine manur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Sugarcane vinasse application has demonstrated potential benefits in mitigating sodium toxicity in soil. Gutieŕrez et al (2016) found that applying vinasse at 10 L ha -1 significantly reduced exchangeable sodium percentage (ESP) by 23.58% and sodium adsorption ratio (SAR) by 65.83% in sodic soils. This effect is attributed to the enrichment of soil with divalent cations, primarily calcium (Ca 2+ ), as highlighted by Kopittke (2012), Tobe et al (2003), andRahimi et al, 2000. Aluminium, another beneficial nutrient, can be toxic to many crops and soil microorganisms (Aggarwal et al, 2015;Bojoŕquez-Quintal et al, 2017).…”
Section: Role Of Vinasse and Molasses In Enhancing Environmental Reme...mentioning
confidence: 99%
See 1 more Smart Citation
“…Sugarcane vinasse application has demonstrated potential benefits in mitigating sodium toxicity in soil. Gutieŕrez et al (2016) found that applying vinasse at 10 L ha -1 significantly reduced exchangeable sodium percentage (ESP) by 23.58% and sodium adsorption ratio (SAR) by 65.83% in sodic soils. This effect is attributed to the enrichment of soil with divalent cations, primarily calcium (Ca 2+ ), as highlighted by Kopittke (2012), Tobe et al (2003), andRahimi et al, 2000. Aluminium, another beneficial nutrient, can be toxic to many crops and soil microorganisms (Aggarwal et al, 2015;Bojoŕquez-Quintal et al, 2017).…”
Section: Role Of Vinasse and Molasses In Enhancing Environmental Reme...mentioning
confidence: 99%
“…Additionally, the byproducts stimulate microbial-induced calcium precipitation, promoting the formation of stable soil aggregates (Nikseresht et al, 2020;Romano et al, 2020;Behzadipour and Sadrekarimi, 2021;Saneiyan et al, 2021). The application of vinasse has been associated with increased soil thermal conductivity, reduced soil bulk density, and increased soil porosity, all of which contribute to improved soil quality and plant growth (Place et al, 2008;Gutieŕrez et al, 2016;Eissa, 2017).…”
Section: The Influence Of Molasses and Vinasse On Soil Propertiesmentioning
confidence: 99%